LEARNERS’ PERCEPTION OF THE USE OF LOCAL-BASED DIGITAL STORYTELLING ON LEARNING RESILIENCE AND LEARNING AUTONOMY - Ryani Yulian; Ufi Ruhama'; Yuniarti Yuniarti (FKIP UM Pontianak, 2023)
The study aimed to examine the learners’ perception of the use of local-based digital storytelling on learning resilience and learning autonomy. Perceived ideas were purposively taken from 30 learners who experienced a local-based digital storytelling-making process in an English for Communication in Academic Settings class. The findings of the study revealed that learners perceived digital storytelling as highly motivating and useful for learning resilience and learning autonomy. They indicated a need for more local-based digital storytelling in their language learning, recognizing its value in understanding the necessity of resilience in overcoming adversities. Learners believe that digital storytelling practice improves their creativity, critical thinking, and information retention, hence strengthening the connections between real-life experiences and academic knowledge. The collaborative and participatory aspect of digital storytelling enhances students' self-learning and ownership of learning autonomy. Examining learners’ perceptions can be useful to articulate their ideas about the language learning process related to learning strategies, strengths and weaknesses to improve. It can also assist language educators to promote inclusivity in the classroom by providing insight into the individual qualities of learners.